Biochar-Based Subsurface-Flow Wetland from Crumb Rubber Scrap in Treatment of Landfill Leachate - Anggrika Riyanti; Hadrah Hadrah; Bimastyaji Surya Ramadan; Iwan Saputra; Monik Kasman; Riska Rahmah Dani Fitri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Leachate resulting from the decomposition of organic waste is still a challenging problem, especially in landfill management.  Constructed wetlands (CW) are effective, economical, and environmentally friendly options to treat landfill leachate. Biochar added into CW as a pollutant adsorbent in leachate treatment.  This study aimed to determine the effectiveness of sub-surface flow CW amended with biochar in reducing leachate pollutants. Biochar was synthesized from crumb rubber scrap waste using pyrolysis. The variation biochar in CW i.e. CW0 without biochar as a control system, CW1 10% biochar, CW2 20% biochar, and CW3 30% biochar.  Leachate samples flowed into each CW reactor for 10 days of retention time.  The scanning electron showed that the biochar pores ranged from 5-10 կm, containing elements of C, O, Ca, N, Mg, Al, Si, and Fe.  Some elements have greater cumulative mass and atomic percentage values i.e. C 34.51%, O 26.54%, and Ca 21.85%.  The result of CW treatment showed that the CW system was able to remove 76-88% BOD5, 70-87% COD, and 67-81% TSS.  The addition of biochar in CW increased pollutant removal by 7-14%, showing that biochar is able to increase pollutant adsorption in wastewater and improve CW performance. Furthermore, converting organic waste into biochar is highly recommended as a sustainable way to generate useful resources.